PD-1 restraint of regulatory T cell suppressive activity is critical for immune tolerance - Tan, Catherine L; Kuchroo, Juhi R; Sage, Peter T; Liang, Dan; Francisco, Loise M; Buck, Jessica; Thaker, Youg Raj; Zhang, Qianxia; McArdel, Shannon L; Juneja, Vikram R; Lee, Sun Jung; Lovitch, Scott B; et al. (The Journal of experimental medicine, 2021)
Inhibitory signals through the PD-1 pathway regulate T cell activation, T cell tolerance, and T cell exhaustion. Studies of PD-1 function have focused primarily on effector T cells. Far less is known about PD-1 function in regulatory T (T reg) cells. To study the role of PD-1 in T reg cells, we generated mice that selectively lack PD-1 in T reg cells. PD-1-deficient T reg cells exhibit an activated phenotype and enhanced immunosuppressive function. The in vivo significance of the potent suppressive capacity of PD-1-deficient T reg cells is illustrated by ameliorated experimental autoimmune encephalomyelitis (EAE) and protection from diabetes in nonobese diabetic (NOD) mice lacking PD-1 selectively in T reg cells. We identified reduced signaling through the PI3K-AKT pathway as a mechanism underlying the enhanced suppressive capacity of PD-1-deficient T reg cells. Our findings demonstrate that cell-intrinsic PD-1 restraint of T reg cells is a significant mechanism by which PD-1 inhibitory signals regulate T cell tolerance and autoimmunity.